TO STUDY AND EXPLORE THE CUSTOMER ATTITUDE TOWARDS SAFER NATURAL PRODUCTS QUALITATIVELY FOR FMCG FOODSECTOR ECO-BRANDINGIN INDIAN SCENARIO - Dr. Aparna Goyal (International Journal of Research Science and Management, 2017)
As a minimum requirement people need and want to see clearly the food's description, the brand, the use by/ best before date, and the price. Respondents know that words lie, pictures mislead, and marketers tell stories. Consequently, the overriding principle of the product description and food packaging is to let the product offer direct sensory evidence of its appearance and qualities. In the super market, the sight of food is the primary indexical evidence available to the customer. Transparency/visibility becomes an overriding goal in food packaging because it enables direct, sensory product evidence; validation of benchmark claims; comparison to competitor product; and imagined consumption. The accompanied and eye-tracked shops demonstrated that respondents are very tactile with food where they can be – e.g. with fruit and vegetables - and the transparency of meat packaging was especially important and used by respondents as a shortcut for judging food benchmark. Price can eclipse other aspects of the Brand information, especially for lower income respondents. Those with high income displayed different attitudes to those with lower income in terms of the perceived options available. Respondents in lower paid jobs paid more attention to special price offers, and thus respectively paid less attention to food primary, secondary and tertiary packs directly. Individual dietary requirements are key in determining the use of and engagement with different elements of food Brand information. The level and extent of information required is often driven by specific dietary needs or underlying health conditions – e.g. health (allergies, high blood pressure), religion (kosher), or morals/choice/lifestyle (vegetarian, vegan, dieting), and thus a need to hone in on particular information. Respondents avoid reading the back of food packs by using words or symbols on the front as ‘beacons’ to quickly guide shopping. Any particular respondent has his or her own agenda and is unlikely to be interested in the totality of primary, secondary and tertiary packs. The respondent’s goal is to exercise their selective attention, securing key elements of information, while ignoring the broad mass of material (i.e. they develop Short cut for information). Some participants reported struggling with the volume of information provided on food packages suggesting that there was simply too much. The challenge is that different respondents think that different elements are superfluous, and that different individual elements constitute overcrowding or overshadowing to different respondents. Because it serves, a range of descriptive tasks (e.g. detailing food ingredients and constituents, explaining how to cook the food) food primary, secondary and tertiary packs is a hybrid text, presenting a range of different vocabularies and sets of assumptions. Some of the component messages may be patronizingly simple whereas some descriptions of ingredients and constituents may presume a level of knowledge that the general respondent may lack. It has been found that particularly w.r.t. the food industry, there is relatively less involvement during purchasing and evidence shows what all information customers actually look for when they buy, vis-a-vis what they say they look at.